Clinical outcomes of dysphagia in patients with acute stroke in Oman in 2021 - Raya Al-Mamari; Eilean Rathinasamy Lazarus; Maryam Alharrasi; Huda Al-Noumani; Omar Alzaabi (Kashan University of Medical Sciences, 2024)
Background: Dysphagia is the most common and significant neuromuscular disorder following a massive stroke. Patients with dysphagia are at a higher risk of developing pneumonia, experiencing prolonged hospital stays, and requiring nasogastric tube placement, which can increase post-stroke morbidity and mortality.Objectives: This study aimed to investigate the effects of post-stroke dysphagia on various clinical outcomes in acute stroke patients. These outcomes included the degree of impairment, mortality rate, presence of nasogastric tube (NGT), incidence of stroke-associated pneumonia, and duration of hospitalization.Methods: The study employed a cross-sectional design, involving a sample of 274 patients with acute stroke admitted to two tertiary hospitals in Oman over a six-month period. The researcher utilized a non-probability convenience sampling technique from June 2 to November 21, 2021. The Modified Rankin Scale was used to assess the level of impairment, including death upon discharge. The Glasgow Coma Scale and Gugging Swallowing Screen were employed to evaluate dysphagia. Data analysis was conducted using SPSS version 23 software, which included descriptive analysis, correlations, and regression analysis, with statistical significance set at p<0.05.Results: The study included 274 participants, comprising 170 males (62%), with a mean age of 61.14±14.83 years. A substantial proportion (70.1%) experienced dysphagia. Approximately 35% had a history of previous strokes, and comorbidities such as hypertension (71.9%) and diabetes mellitus (58.4%) were prevalent. Smoking, alcohol consumption, and obesity were noted in subsets of participants. Most had ischemic strokes (81.8%) with varied locations. Glasgow Coma Scale scores varied, with 42.3% scoring 15/15. Thrombolysis/ thrombectomy was performed in 14.9% of cases, and 9.5% experienced hemorrhagic transformation. A significant correlation was found between dysphagia and the prolonged use of NGT during hospitalization and upon discharge (p<0.001). Dysphagia was also linked to longer hospital stays and higher levels of impairment, including increased mortality rates and the incidence of stroke-related pneumonia (p<0.001).Conclusion: Dysphagia is prevalent among acute stroke patients in Oman and significantly impacts post-stroke outcomes, including prolonged hospitalization, increased mortality rates, heightened levels of impairment, and the need for nasogastric tube placement, as well as the occurrence of stroke-related pneumonia. This study emphasizes the importance of implementing routine dysphagia screening and multidisciplinary management teams for acute stroke patients, along with establishing standardized protocols and ongoing training for healthcare providers in Oman.